Reflectance measurements from within and around a supraglacial stream in Southwest Greenland (67.15N, 50.00W) collected in August 2019 - Sasha Leidman; Asa Rennermalm; McKenzie Skiles (Arctic Data Center, 2023)
This dataset includes two files: 1. ASD_SedCover_2019_Published_Reflectance; Reflectance measurements in each wavelength between 350-2500 nm (nanometers) for 41 sites. 2. ASD_SedCover_2019_Published_Summary; GPS locations, sediment cover, and average reflectance values for each site. Measurements were georeferenced using a Trimble R7 PPK (post-processed kinematic) GNSS (Global navigation satellite system) and water depth was recorded with a ruler when applicable. Images of the sample area were collected in triplicate and converted to black and white to determine the percent sediment cover for the observation window. These measurements were used to deduce the relationship between sediment cover and reflectance. More details are provided in Leidman et al. (2023). Reference: Leidman, S. Z., Rennermalm, Å. K., Muthyala, Skiles, S. M., and Getraer, A. (2023). Intra-Seasonal Variability in Supraglacial Stream Sediment on the Greenland Ice Sheet. Frontiers of Earth Science: Cryospheric Science.